The adoption of dog-assisted activity in the university environment as a tool to minimize the stress of academics - Cintra, Ana Carolina Rizzon; Junior, Pedro Vicente Michelotto; Weber, Saulo Henrique; Michelotto, Ana Lucia Lacerda (Seven Editora, 2023)
This study examined the impact of Animal-Assisted Intervention (AAI), specifically contact with a therapist dog, on reducing stress among university students. The research was conducted at the Pontifical Catholic University of Paraná (PUCPR) in 2021 and involved nine medical students enrolled at the university. Inclusion criteria included no fear of or allergy to dogs. The results revealed that interaction with the dog had positive effects on reducing the students’ stress. Although there were no significant changes in heart rate, systolic blood pressure decreased significantly after the interaction. In addition, the students’ levels of stress, anxiety, tension and worry decreased after the session with the dog, and no student reported elevated levels of these parameters after the interaction. The students also mentioned that, during the interaction with the dog, they were able to momentarily forget their worries, which suggests a temporary relief from stress. In addition, the majority of participants stated that they would recommend the Animal Assisted Intervention. These results indicate that AAI, even in short sessions, can be effective in reducing stress among university students. The presence of a therapist dog creates a pleasant social atmosphere and offers emotional support, improving students’ mental health. Therefore, the implementation of animal-assisted therapy programs in academic settings can be beneficial in helping undergraduate students cope with stress and anxiety, promoting a healthier learning environment. DOI:https://doi.org/10.56238/innovhealthknow-052